Numerical investigation of magnetic nanoparticles trajectories for magnetic drug targeting - Shazri, Syireen; Idres, Moumen (Institute of Physics Publishing, 2017)
In this work, the trajectories and capturing of magnetic nanoparticles coated with drug agent are investigated for drug targeting application. Nanoparticles are injected at the entrance of a microvessel and captured by a permanent magnet located at a specified location where tumor exists. The problem is divided into two steps; blood flow solution and nanoparticles trajectory solution. The blood flow in microvessel is obtained both analytically and numerically. Integration of nanoparticles equations of motion to obtain the trajectories is performed using both Matlab and ANSYS Fluent. Discrete Phase Model (DPM) in ANSYS Fluent is used for nanoparticles tracking. The dominant magnetization and drag forces acting on magnetic particles are incorporated to study the trajectories of magnetic particles. Parametric studies for steady flow with single point and multiple point injections are conducted. This includes varying particle diameter and magnet location. Critical minimum diameter for capturing is predicted. Capturing efficiency is reported for all cases. It is found that particle trajectories are strongly dependent on particle size and location of the magnet. The simulation can be used to determine the optimum particle size for treating a tumor, given its size and location.